A high removal rate nano-alumina-based polishing liquid and preparation method thereof

Through the preparation method of modified nano alumina, the hardness of abrasive particles and corrosion inhibitor corrosion rate are improved, and the melting of cobalt phase and α-phase alumina and graphene composite are combined, the problem of inconsistent abrasive blades of the existing alumina-based polishing liquid is solved. A polishing effect with high removal rate and excellent surface quality is achieved.

CN118222189BActive Publication Date: 2025-02-11HENAN LUNAR NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410334503.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-22
Publication Date
2025-02-11
Estimated Expiration
2044-03-22

AI Technical Summary

Technical Problem

The abrasive blade height of the existing alumina-based polishing liquid is inconsistent, resulting in deep scratches and large subsurface damage on the surface of the object after processing, and the removal rate is low, extending the polishing time of the workpiece.

Method used

Through the preparation method of modified nanoalumina, the hardness of abrasive particles and the static corrosion rate of the corrosion inhibitor are improved, and the melting of cobalt phase and α-phase alumina and the composite of graphene and nanoalumina are prepared to prepare nanos with higher hardness. Alumina-based polishing liquid.

Benefits of technology

It improves the removal rate of polishing liquid, ensures the surface quality of the processed materials, avoids scratches and subsurface damage, and shortens the polishing time of the workpiece.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004754618140000071
    Figure BDA0004754618140000071
Patent Text Reader

Abstract

The invention discloses a high removal rate nano-alumina-based polishing liquid and a preparation method thereof. The polishing liquid comprises the following raw materials by weight: 2-6 parts of an oxidant, 4-10 parts of abrasive grains, 0.9-1.5 parts of a complexing agent, 1-2.2 parts of a corrosion inhibitor, and 70-80 parts of deionized water; wherein the oxidant is a 3-5wt% hydrogen peroxide solution or potassium permanganate, the abrasive grains are modified nano-alumina, and the corrosion inhibitor is grafted aminomethyl propanol. The invention improves the removal rate by increasing the hardness of the abrasive grains and the static corrosion rate of the corrosion inhibitor, and ensures the surface quality of the processed material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of precision grinding and polishing, and specifically relates to a high-removal rate nano-alumina-based polishing liquid and a preparation method thereof. Background Art

[0002] Chemical mechanical polishing is a global flattening technology widely used in the industry. It can achieve ultra-precision processing of many materials. It combines the chemical action of various additives in the polishing liquid with the mechanical action of abrasive particles to achieve material removal and surface flattening.

[0003] Polishing fluid is generally a mixture of ultra-fine solid grinding materials and chemical additives. On the one hand, it uses abrasive grinding to achieve mechanical removal; on the other hand, it uses complexing agents and corrosion inhibitors to achieve chemical corrosion and passivation protection of materials, so that the material can obtain better surface quality. However, the processing method of free abrasives used in polishing fluids leads to low material removal rate and prolongs the polishing time of workpieces.

[0004] Patent CN106221587B discloses an aluminum oxide-based chemical mechanical polishing liquid, which provides a polishing effect with a good removal rate while also being sterile and weakly irritating. However, the abrasive particles used in the polishing liquid contain silicon oxide powder, silicon nitride powder and aluminum oxide powder. Abrasive particles of different hardness may cause deeper scratches and larger sub-surface damage on the surface of the object after processing due to inconsistent abrasive blade heights. Summary of the invention

[0005] To solve the above problems, the present invention provides a high-removal rate nano-alumina-based polishing liquid and a preparation method thereof, which improves the removal rate by increasing the hardness of the abrasive particles and the static corrosion rate of the corrosion inhibitor, and ensures the surface quality of the processed material.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is:

[0007] On one hand, the present invention provides a high-removal rate nano-alumina-based polishing liquid, which comprises the following raw materials by weight: 2-6 parts of an oxidant, 4-10 parts of abrasive particles, 0.9-1.5 parts of a complexing agent, 1-2.2 parts of a corrosion inhibitor and 70-80 parts of deionized water.

[0008] The oxidant is 3-5wt% hydrogen peroxide solution or potassium permanganate.

[0009] The abrasive grains are modified nano-alumina.

[0010] The corrosion inhibitor is grafted aminomethyl propanol.

[0011] The preparation steps of the modified nano-alumina are as follows:

[0012] S1. Powdered aluminum oxide and deionized water are prepared into a mixed solution, the pH of the mixed solution is adjusted to 3-4 with hydrochloric acid, and then ultrasonically treated for 1-3 hours to obtain a mixture A;

[0013] S2, dispersing the graphene powder in deionized water and ultrasonically treating for 4-6 hours to obtain a mixture B;

[0014] S3, stirring the mixture A in step S1 and the mixture B in step S2 for 1-2 hours, then ultrasonically treating for 30-60 minutes, and vacuum freeze-drying for 20-28 hours to obtain composite particles;

[0015] S4, ball-milling the cobalt powder and the composite particles in step S3 at a speed of 40-80 r / min for 40-55 h. After the ball-milling is completed, washing and drying, adding glycerol and stirring for 20-40 min, and then calcining. The calcination temperature is 1200-1500° C., the heating rate is 4-6° C. / min, and the mixture is kept warm for 1-3 h and then cooled to room temperature to obtain modified nano alumina.

[0016] In the step S1, the powdered aluminum oxide is in the α phase.

[0017] The concentration of the mixed solution in step S1 is 0.0075-0.0085 g / mL.

[0018] The mass ratio of cobalt powder to composite particles in step S4 is 1:(2-4).

[0019] The ball milling in step S4 is wet rolling ball milling, and the ball milling medium is anhydrous ethanol.

[0020] The complexing agent is one or more of mannitol, glycine and xylitol.

[0021] The preparation steps of the grafted aminomethyl propanol are as follows:

[0022] Stir N,N-carbonyldiimidazole and dodecyl phosphate monoester at 50-70°C for 40-80 minutes, then drop aminomethyl propanol into it, and continue to react for 2-4 hours after the dropwise addition is completed to obtain grafted aminomethyl propanol.

[0023] The molar ratio of the N,N-carbonyldiimidazole, dodecyl phosphate monoester and aminomethyl propanol is (0.95-1.05):1:(1.3-1.5).

[0024] Another aspect of the present invention provides a method for preparing a high removal rate nano-alumina-based polishing liquid, comprising the following steps:

[0025] After the abrasive grains and deionized water are uniformly stirred, a complexing agent, an oxidant and a corrosion inhibitor are added in sequence, and stirring is continued for 30-50 minutes to obtain a nano-alumina-based polishing liquid with a high removal rate.

[0026] When nano-alumina is used for grinding and polishing, its nano-microcrystalline structure is not easy to scratch objects, but the finer particle size leads to a low removal rate, which prolongs the processing time of the workpiece and increases the processing cost. For this reason, the polishing time can be accelerated by increasing the hardness of nano-alumina while maintaining the nano-microcrystalline structure.

[0027] Cobalt has two crystal structures: hexagonal close-packed hcp-Co and face-centered cubic fcc-Co. At high temperatures, part of the hcp-Co phase that is stable at room temperature will transform into the fcc-Co phase. Through melting, the Al and O elements in the α-phase alumina can be dissolved in the fcc-Co phase and the high thermal expansion coefficient of Co can be used to put it in a tensile state, thereby maintaining the stability of the fcc-Co phase during cooling, thereby improving the hardness and wear resistance of nano-alumina.

[0028] However, simply mixing and calcining the two substances will produce powder with uneven particles, which will cause deeper scratches and larger sub-surface damage on the surface of the processed object due to inconsistent abrasive edge height when used as abrasive particles in polishing liquid. In addition, since the grain size of modified nano-alumina is proportional to the mean free path of the cobalt phase, and the mean free path of the cobalt phase is negatively correlated with the hardness, the smaller the grain size, the smaller the mean free path of the cobalt phase, and the higher the hardness of the modified nano-alumina.

[0029] In order to ensure the acquisition of fine grains of modified nano-alumina, the present invention firstly compounds graphene with nano-alumina. On the one hand, the surface energy of nano-alumina is reduced by the graphene powder adsorbed on the nano-alumina particles, thereby hindering the process of particle dissolution and re-precipitation; on the other hand, the melting of nano-alumina in the cobalt phase is reduced by the melting of graphene in the cobalt phase, thereby slowing down the melting and recrystallization process of nano-alumina particles; secondly, the precipitation of graphene on the grain boundary of nano-alumina can hinder the diffusion migration of the grain boundary. The above three aspects effectively inhibit the growth of grains, so that the modified nano-alumina not only improves the hardness, but also ensures the average size, providing an excellent polishing effect for the surface treatment of objects.

[0030] Researchers have found that excessively increasing the hardness of abrasive particles can easily lead to damage to the surface of certain brittle materials. Therefore, in order to further improve the removal efficiency of the polishing liquid, the present invention improves the static corrosion rate by modifying the corrosion inhibitor to ensure that a solid-phase reaction occurs at the actual contact point between the surface of the material and the abrasive particles during the polishing process, and the product of the solid-phase reaction has a poor binding force with the parent material and is easily removed by mechanical force. To ensure the removal effect, the present invention regulates the raw materials in the corrosion inhibitor modification process to ensure the generation of highly active intermediate acyl imidazoles and avoid the generation of urea-based byproducts.

[0031] The present invention uses a green and environmentally friendly complexing agent, which can form an easily removable complex with metal ions, and the hydroxyl structure inside the complexing agent can further increase the interface reaction rate between the polishing liquid and the surface of the treated object during the processing. The combination of the two improves the polishing removal rate.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The present invention provides a nano-alumina-based polishing liquid with high hardness, which, when used for grinding and polishing, not only improves the removal rate but also ensures the surface quality of the processed material.

[0034] 2. The present invention utilizes the lattice effect to enhance the hardness of nano-alumina by melting the cobalt phase and the α-phase alumina; and avoids the occurrence of grain unevenness during melting by first compounding graphene and nano-alumina, thereby ensuring the generation of high-hardness modified nano-alumina.

[0035] 3. The present invention improves the static corrosion rate by modifying aminomethyl propanol, thereby further improving the removal efficiency of the polishing liquid. DETAILED DESCRIPTION

[0036] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0037] In order to facilitate those skilled in the art to implement the present invention, some raw materials and manufacturers of the embodiments and comparative examples are described as follows:

[0038] Powdered aluminum oxide was purchased from Hangzhou Hengna New Materials Co., Ltd. with a particle size of 100 nm;

[0039] Graphene powder was purchased from Changzhou Sixth Element Materials Technology Co., Ltd.;

[0040] Cobalt powder was purchased from Beijing Dekedaojin Technology Co., Ltd. with a size of 50 nm.

[0041] Preparation Example 1

[0042] The preparation steps of modified nano-alumina-A are as follows:

[0043] S1. 8 g of powdered aluminum oxide and 1000 mL of deionized water were mixed into a mixture, the pH of the mixture was adjusted to 3.4 with 1 mol / L hydrochloric acid, and then ultrasonically treated for 2 h to obtain a mixture A;

[0044] S2, dispersing 5 g of graphene powder in 1000 mL of deionized water and ultrasonically treating for 4 h to obtain a mixture B;

[0045] S3, stirring the mixture A in step S1 and the mixture B in step S2 for 1.5 h, then ultrasonically treating for 30 min, and vacuum freeze-drying for 24 h to obtain composite particles;

[0046] S4. Wet-roll ball mill 5 g of cobalt powder and 15 g of the composite particles in step S3 at a speed of 60 r / min for 48 h. The ball milling medium is 40 g of anhydrous ethanol. After the ball milling is completed, wash and dry, add 8 g of glycerol and stir for 30 min, then calcine. The calcination temperature is 1400° C., the heating rate is 5° C. / min, and the mixture is kept warm for 2 h and then cooled to room temperature to obtain modified nano-alumina-A.

[0047] Preparation Example 2

[0048] The preparation steps of modified nano-alumina-B are as follows:

[0049] The difference between this preparation example and preparation example 1 is that the amount of powdered aluminum oxide used in step S1 is 7 g.

[0050] Preparation Example 3

[0051] The preparation steps of modified nano-alumina-C are as follows:

[0052] The difference between this preparation example and preparation example 1 is that the amount of powdered aluminum oxide used in step S1 is 9 g.

[0053] Preparation Example 4

[0054] The preparation steps of modified nano-alumina-D are as follows:

[0055] 13 g of powdered alumina and 5 g of cobalt powder were wet-rolled by ball milling at a speed of 60 r / min for 48 h. The ball milling medium was 40 g of anhydrous ethanol. After the ball milling was completed, they were cleaned and dried, and 8 g of glycerol was added and stirred for 30 min. Then, they were calcined at a calcination temperature of 1400°C and a heating rate of 5°C / min. After keeping warm for 2 h, they were cooled to room temperature to obtain modified nano-alumina-D.

[0056] Preparation Example 5

[0057] The preparation steps of grafted aminomethyl propanol-A are as follows:

[0058] 162 g of N,N-carbonyldiimidazole and 266 g of dodecyl phosphate monoester were stirred at 60° C. for 60 min, and then 120 g of aminomethyl propanol was dropped into the mixture. After the addition was completed, the reaction was continued for 3 h to obtain grafted aminomethyl propanol-A.

[0059] Preparation Example 6

[0060] The preparation steps of grafted aminomethyl propanol-B are as follows:

[0061] The difference between this preparation example and preparation example 5 is that the amount of N,N-carbonyldiimidazole used is 148 g.

[0062] Preparation Example 7

[0063] The preparation steps of grafted aminomethyl propanol-C are as follows:

[0064] The difference between this preparation example and preparation example 5 is that the amount of N,N-carbonyldiimidazole used is 175 g.

[0065] Example 1

[0066] A high-removal rate nano-alumina-based polishing liquid comprises the following raw materials, measured by weight: 5 parts of 4wt% hydrogen peroxide solution, 7 parts of modified nano-alumina-A, 1.2 parts of mannitol, 1.8 parts of grafted aminomethyl propanol-A and 75 parts of deionized water.

[0067] The method for preparing a high removal rate nano-alumina-based polishing liquid in this embodiment comprises the following steps:

[0068] After the modified nano-alumina-A and deionized water are uniformly stirred, mannitol, 4wt% hydrogen peroxide solution and grafted aminomethyl propanol-A are added in sequence, and stirring is continued for 40 minutes to obtain a nano-alumina-based polishing liquid with a high removal rate.

[0069] Example 2

[0070] A high-removal rate nano-alumina-based polishing liquid comprises the following raw materials, measured by weight: 4 parts of 4wt% hydrogen peroxide solution, 6 parts of modified nano-alumina-A, 1.0 part of mannitol, 1.3 parts of grafted aminomethyl propanol-A and 70 parts of deionized water.

[0071] The method for preparing a high removal rate nano-alumina-based polishing liquid in this embodiment comprises the following steps:

[0072] After the modified nano-alumina-A and deionized water are uniformly stirred, mannitol, 4wt% hydrogen peroxide solution and grafted aminomethyl propanol-A are added in sequence, and stirring is continued for 40 minutes to obtain a nano-alumina-based polishing liquid with a high removal rate.

[0073] Example 3

[0074] A high-removal rate nano-alumina-based polishing liquid comprises the following raw materials, measured by weight: 6 parts of 4wt% hydrogen peroxide solution, 8 parts of modified nano-alumina-A, 1.5 parts of mannitol, 2.0 parts of grafted aminomethyl propanol-A and 80 parts of deionized water.

[0075] The method for preparing a high removal rate nano-alumina-based polishing liquid in this embodiment comprises the following steps:

[0076] After the modified nano-alumina-A and deionized water are uniformly stirred, mannitol, 4wt% hydrogen peroxide solution and grafted aminomethyl propanol-A are added in sequence, and stirring is continued for 40 minutes to obtain a nano-alumina-based polishing liquid with a high removal rate.

[0077] Example 4

[0078] This embodiment provides a high removal rate nano-alumina-based polishing liquid and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified nano-alumina-A in the raw material is replaced by an equal portion of modified nano-alumina-B.

[0079] Example 5

[0080] This embodiment provides a high removal rate nano-alumina-based polishing liquid and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified nano-alumina-A in the raw material is replaced by an equal portion of modified nano-alumina-C.

[0081] Example 6

[0082] This embodiment provides a high removal rate nano-alumina-based polishing liquid and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified nano-alumina-A in the raw material is replaced by an equal portion of modified nano-alumina-D.

[0083] Example 7

[0084] This embodiment provides a high removal rate nano-alumina-based polishing liquid and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that: the grafted aminomethyl propanol-A in the raw material is replaced by an equal portion of grafted aminomethyl propanol-B.

[0085] Example 8

[0086] This embodiment provides a high removal rate nano-alumina-based polishing liquid and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the grafted aminomethyl propanol-A in the raw material is replaced by an equal portion of grafted aminomethyl propanol-C.

[0087] Comparative Example 1

[0088] This comparative example provides a high removal rate nano-alumina-based polishing liquid and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that: the grafted aminomethyl propanol-A in the raw material is replaced by an equal portion of aminomethyl propanol.

[0089] Comparative Example 2

[0090] This comparative example provides a high removal rate nano-alumina-based polishing liquid and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified nano-alumina-A in the raw material is replaced by an equal portion of powdered alumina.

[0091] Performance Testing:

[0092] 1. Hardness test

[0093] The hardness of the abrasive particles in each embodiment and comparative example was tested using a Nano Indenter XP nanohardness tester, with the indentation depth set to 1.5 μm. The nanohardness tester automatically calculated the hardness value of the sample in GPa.

[0094] 2. Polishing effect test

[0095] This test uses sapphire wafers as the polishing material, and the main evaluation indicators are material removal rate and surface roughness. The material removal rate is used to evaluate the efficiency of polishing, and the surface roughness is used to evaluate the surface quality of polishing.

[0096] (1) Material removal rate: The mass of the sapphire wafer before and after polishing was measured using a Mettler XS205DU electronic balance. The average of three weighings was used as the calculated value to obtain the mass difference Δm / g before and after polishing. The material removal rate MRR was calculated based on this value. The formula is as follows:

[0097]

[0098] Where MRR is the thickness of the material reduced per unit time (nm / hr), ρ is the density of the sapphire wafer (3.98 g / cm 3 ), s is the polishing area of ​​the sapphire wafer (7.07 cm 2 ), t is the polishing time (hr).

[0099] (2) Surface roughness: Rtec’s MFD-D white light interferometer three-dimensional profiler was used to characterize the surface morphology of the polished sapphire wafer. The surface quality selection range was a square area of ​​60 μm × 60 μm. The wafer surface morphology was scanned by the profiler and analyzed with the image software Gwyddion to calculate the surface roughness Ra.

[0100] The test results are shown in Table 1.

[0101] Table 1 Performance test results

[0102] Hardness(GPa) MRR(nm / hr) Ra(nm) Example 1 9.6 5.6 0.33 Example 2 9.4 5.3 0.38 Example 3 9.1 5.2 0.37 Example 4 8.2 4.4 0.53 Example 5 8.7 3.9 0.57 Example 6 8.9 3.5 0.71 Example 7 9.6 4.7 0.66 Example 8 9.5 4.0 0.68 Comparative Example 1 9.6 3.9 0.62 Comparative Example 2 8.1 3.8 0.49

[0103] It can be seen from the data in Table 1 that both the modification of nano-alumina and the grafting of aminomethyl propanol can improve the removal rate and reduce the surface roughness, but the effect of the former is more prominent than the latter; it can be seen from Examples 1-6 and Comparative Example 2 that the fusion of cobalt phase and α-phase alumina can significantly improve the hardness of nano-alumina, but the ratio of the two phases needs to be controlled to keep the processed surface at a lower roughness; among them, the first composite of graphene and nano-alumina not only improves the removal rate but also reduces the surface roughness of the sapphire wafer. The possible reason is that this method ensures the average particle size of the modified nano-alumina, thereby achieving a contact balance between the nano-alumina with improved hardness and the surface to be treated; it can be seen from Example 1 and Examples 7-8 and Comparative Example 1 that the grafting of aminomethyl propanol can effectively improve the removal rate, and the control of the raw material ratio in the grafting process has a great influence on the removal rate and surface roughness.

[0104] The embodiments described above do not impose any form of limitation on the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A high removal rate nano-alumina-based polishing liquid, characterized in that: The raw materials include, by weight: 2-6 parts of oxidant, 4-10 parts of abrasive, 0.9-1.5 parts of complexing agent, 1-2.2 parts of corrosion inhibitor and 70-80 parts of deionized water; The oxidant is 3-5wt% hydrogen peroxide solution or potassium permanganate; The abrasive grains are modified nano-alumina; The corrosion inhibitor is grafted aminomethyl propanol; The preparation steps of the modified nano-alumina are as follows: S1. Powdered aluminum oxide and deionized water are prepared into a mixed solution, the pH of the mixed solution is adjusted to 3-4 with hydrochloric acid, and then ultrasonically treated for 1-3 hours to obtain a mixture A; S2, dispersing the graphene powder in deionized water and ultrasonically treating for 4-6 hours to obtain a mixture B; S3, stirring the mixture A in step S1 and the mixture B in step S2 for 1-2 hours, then ultrasonically treating for 30-60 minutes, and vacuum freeze-drying for 20-28 hours to obtain composite particles; S4, ball-milling the cobalt powder and the composite particles in step S3 at a speed of 40-80 r / min for 40-55h, washing and drying after ball-milling, adding glycerol and stirring for 20-40min, and then calcining, the calcination temperature is 1200-1500°C, the heating rate is 4-6°C / min, and the temperature is kept for 1-3h and then cooled to room temperature to obtain modified nano-alumina; In step S1, the powdered aluminum oxide is an α phase; The preparation steps of the grafted aminomethyl propanol are as follows: N, N-carbonyl diimidazole and dodecyl phosphate monoester were mixed at 50-70 o C and stirred for 40-80 min, then aminomethyl propanol was added dropwise, and the reaction was continued for 2-4 h after the addition was completed to obtain grafted aminomethyl propanol; The molar ratio of the N,N-carbonyldiimidazole, dodecyl phosphate monoester and aminomethyl propanol is (0.95-1.05):1:(1.3-1.5); The complexing agent is one or more of mannitol, glycine and xylitol.

2. The high removal rate nano-alumina-based polishing liquid according to claim 1, characterized in that: The concentration of the mixed solution in step S1 is 0.0075-0.0085 g / mL.

3. The high removal rate nano-alumina-based polishing liquid according to claim 1, characterized in that: The mass ratio of cobalt powder to composite particles in step S4 is 1:(2-4).

4. The high removal rate nano-alumina-based polishing liquid according to claim 1, characterized in that: The ball milling in step S4 is wet rolling ball milling, and the ball milling medium is anhydrous ethanol.

5. A method for preparing the high-removal rate nano-alumina-based polishing liquid according to any one of claims 1 to 4, the preparation steps being as follows: after the abrasive particles and deionized water are uniformly stirred, a complexing agent, an oxidant and a corrosion inhibitor are added in sequence, and stirring is continued for 30-50 minutes to obtain the high-removal rate nano-alumina-based polishing liquid.

Citation Information

Patent Citations

  • A kind of aluminum oxide-based chemical mechanical polishing fluid

    CN106221587B

  • Sapphire rough polishing solution and preparation method thereof

    CN110003797A

  • Micro-nano composite ceramic cutter material and preparation method thereof

    CN110330318A